First record of Anatrachyntis badia (Hodges, 1962) (Lepidoptera Cosmopterigidae) in Italy (Bollettino di zoologia agraria e bachicoltura, 2024)
The study of entomofauna of ornamental plants in various cities of Sicily and Calabria led to the discovery of the microlepidoptera Anatrachyntis badia (Hodges, 1962). This North American species is presently distributed in different biogeographical world regions, where it feeds on numerous hosts (cones of conifers infested by fungal agents or other insects, blossoms of coconut, elm leaves, fruits of lime, grapefruit, banana, cabbage etc.). The species was recorded for the first . time in Sicily and Calabria and was feeding on leaves of Cycas revoluta Thunberg and C. circinalis L.
Keywords: Anatrachyntis badia; Italy; new record; Cycas spp.; ornamental plants